Teachers’ Perception of an Online Learning System - Kuswatun Hasanah; Supentri Supentri; Sri Erlinda (Universitas Negeri Malang, 2021)
This study is aimed to monitor teachers perception of an online learning system during the pandemic covid-19 at SMPN 4 Mandau. This study used a descriptive-quantitative design. In the data collection technique, it used observation, an online questionnaire consists of indicators with 20 questions and interviews. The population of this study is all teachers at SMP N 4 Mandau, Bengkalis Regency, Riau Province. Then, the samples were taken by using the total sampling technique. The result showed that the respondents answered Strongly Agree and Agree referred to 66.71 percent with a presence in the range of 50.01-68.00 percent. Thus, teachers perception of online learning at SMP N 4 Mandau was Quite Good.